Ghost spasticity in multiple sclerosis. (April 2020) - Trompetto, Carlo; Currà, Antonio; Puce, Luca; Mori, Laura; Pallecchi, Ilaria; Gazzola, Paola; Fabbri, Sabrina; Uccelli, Antonio; Novi, Giovanni; Crisafulli, Oscar; Serrati, Carlo; Marinelli, Lucio
Abstract: Spasticity is the velocity-dependent hypertonia frequently encountered in patients affected by Upper Motor Neuron Syndrome. It is due to a tonic stretch reflex, which is evoked in patients at rest. The aim of this study, performed using surface electromyography (EMG), was to investigate stretch reflex excitability in the hamstrings muscles of patients affected by progressive Multiple Sclerosis (MS) and to correlate EMG results with clinical findings. Thirty patients and 20 age-matched healthy controls were investigated. EMG activity was recorded from biceps femoris muscle with the patient at rest. To stretch hamstrings muscles, the patient's leg was manually moved from maximal flexion to maximal extension at 3 different velocities to investigate both phasic and tonic stretch reflex. Only 7 patients were affected by hypertonia of the hamstrings; 4 of them showed muscle contracture. A tonic stretch reflex was present in the vast majority of the recruited patients, whether they presented hypertonia of the hamstrings or not. Tonic stretch reflex is often present in the hamstrings muscles of progressive MS patients without producing increased muscle tone. This "ghost spasticity" is likely to be, for its intrinsic features, an important risk factor for the development of contractures in the hamstrings muscles.